Model Konseling Kelompok Cognitive Behavior untuk Penanganan Self-esteem Siswa SMK - Bakhrudin, Habsy All (Jurnal Bimbingan dan Konseling Terapan, 2017)
This study aims to test the effectiveness of Cognitive Behavior Group Counseling to improve Self-Esteem vocational students. This study, using experimental design with pretest and posttest control group design. Based on the measurement results of self-esteem inventory netted twelve students identified as students who have low self-esteem characteristics. Subsequently the selection of subjects for the experimental and control groups was conducted randomly with a total of six students for each group. There are two types of instruments used are treatment and measurement instruments. The treatment instrument is guidance on the implementation of Cognitive Behavior Group Counseling, while the measurement instrument is self-esteem inventory which has a total grain validity value with R value above 0.32, and reliability of 0.945 can be concluded that reliable and feasible self-esteem inventory is used as research instrument . Data were analyzed by non-parametric statistics Two Independent Sample Test Mann Whitney. The result of hypothesis is Z value is -2.242 and Asymp number. Sig. (2-tailed) is 0.025 <0.05, then Ho is rejected, meaning Cognitive Behavior Group Counseling to improve Self-Esteem vocational students. Based on the results of the research can be submitted suggestions: 1) for Counselors: Cognitive Behavior Group Counseling can be applied to improve the Self-Esteem students of SMK, and as a basis for understanding the development aspects of vocational students, 2) Further Research: This research apply Cognitive Behavior Group Counseling with technique Cognitive restructuring, problem solving and home duties, for further research to test their effectiveness by using other relevant techniques.